2016
DOI: 10.1371/journal.pone.0151654
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methodology for Rapid Detection of KRAS Mutation Using PNA-LNA Mediated Loop-Mediated Isothermal Amplification

Abstract: Detecting point mutation of human cancer cells quickly and accurately is gaining in importance for pathological diagnosis and choice of therapeutic approach. In the present study, we present novel methodology, peptide nucleic acid—locked nucleic acid mediated loop-mediated isothermal amplification (PNA-LNA mediated LAMP), for rapid detection of KRAS mutation using advantages of both artificial DNA and LAMP. PNA-LNA mediated LAMP reactions occurred under isothermal temperature conditions of with 4 primary prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 28 publications
2
53
0
2
Order By: Relevance
“…S9 † for PAGE analysis of the PCR product). 64 The resulting PCR mixture containing 71-mer singlestranded DNA (Fig. 6A), which is an identical sequence to the targeted mRNA region, was directly assessed using a CHOMS reaction without further manipulations.…”
Section: Resultsmentioning
confidence: 99%
“…S9 † for PAGE analysis of the PCR product). 64 The resulting PCR mixture containing 71-mer singlestranded DNA (Fig. 6A), which is an identical sequence to the targeted mRNA region, was directly assessed using a CHOMS reaction without further manipulations.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, LAMP assays were used to detect the F167Y mutation in Fusarium graminearum and KRAS mutation patients with cancer. 16,17 Additionally, LAMP assays were used to detect the haptoglobin gene deletion in alkaline-denatured blood. 18 In this study, we found that the target sequence was successfully amplified and that the wild type and target could be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…[41] Mutation responsible for cancer development can also be detected by this methodology. [42] In a different context, Centeno-Cuadros et al developed a LAMP protocol for sex determination of raptor species. [43] In comparison with PCR-based methods, LAMP amplification demonstrates better sensitivity and specificity.…”
Section: Loop-mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%